Artificial Intelligence and Sustainable Tourism Planning: A Hetero-Intelligence Methodology Proposal - Eva Maria Buitrago-Esquinas; Rocío Yñiguez-Ovando; Miguel Puig-Cabrera; Margarida Custódio Santos; José António C. Santos (Tourism & Management Studies)
This study explores the growing significance of Large Language Models (LLMs) in tourism, for their current and potential applications. It aims to achieve two primary objectives: first, to develop a novel hetero-intelligence framework merging human and artificial intelligence (AI) to address contemporary sustainability challenges in tourism; second, to validate this framework by applying it to sustainable tourism planning, assessing LLMs' capabilities and limitations. The research employs a hetero-intelligence performance test, contrasting human intelligence and AI contributions in sustainable tourism planning with overtourism as a proxy challenge. Results showed that hetero-intelligence could effectively address sustainability issues in tourism, provided human and AI strengths and weaknesses are understood. LLMs proved useful in diagnosing and proposing solutions for sustainability-related issues. However, a rigorous methodological framework is essential to ensure unbiased outcomes. The research offers practical guidelines for applying this approach and significantly contributes to epistemological and empirical dimensions, providing valuable insights for researchers and tourism planners. The study calls for more empirical research to validate the methodology and explore ethical and legal dimensions, extending hetero-intelligence applications to broader sustainability challenges in tourism.